Strength and Index Properties Analysis of Thermally Generated Silica Fume (TGSF) Infused Organic Soil: Soil Swelling Behavior Treatment Breakdown - M. Sheraz; T. Younas; S. Shah; M. A. Khan; Shah; Ziaullah; S. Khan (Journal of ICT, Design, Engineering and Technological Science, 2020)
This study includes an experimental investigation and dissemination of the stabilization of an expansive land from Nandipur, Punjab, Pakistan using silica smoke Thermally Generated Silica Fume (TGSF). The bright buildings are constantly exposed to structural loads; therefore, repairs and maintenance are due to the cyclic source drying of the underlying expansive floors, caused by watering and drying. There is a growing interest in using industrial waste to reduce soil swelling. In this study, in particular, the stabilizing materials were tested for their suitability as puzzles. After arguing that silica vapor TGSF is sufficiently active, it was used in ratios of 5% TGSF, 10% TGSF, and 15% TGSF, based on the soil dry matter. The physical properties and volume change behavior of the natural soil and the treated soil were investigated. After completing the test program, this includes the grain size distribution, the Atterberg limit, the specific weight, the relationship between moisture and dry density, the Unrestricted Compressive Strength (UCS), and the swell potential. It was concluded that there was a remarkable weakening, especially in the swelling and shrinking behavior. In the end, it was concluded that the addition of 5% TGSF was more effective. It is therefore recommended to mix and compact the expansive soils exposed to light loads such as sidewalks, streets and buildings with a maximum of two stories.